3D printing for CO2 capture and chemical engineering design. Issue 5 (September 2013) - Bara, Jason E.; Hawkins, Christopher I.; Neuberger, David T.; Poppell, Samuel W.
Abstract : Three-dimensional printing is a form of additive manufacturing that allows the fabrication of items directly from digital files, allowing the user to virtually produce any solid object on demand. Three-dimensional printing is already a frequently discussed topic in the mainstream media and is beginning to find a number of applications in research laboratories. The authors have recognized that 3D printing can have many roles in the design of chemical engineering processes as a means of fabricating parts or perhaps entire unit operations. The authors foresee many opportunities for 3D printing as a means of producing novel and advanced components and entire devices for gas treating. Gas treating (i.e. the removal of one or more contaminants from a gaseous mixture) plays a crucial role in many existing and emerging energy-related processes including natural gas sweetening, flue gas desulfurization and pre- and post-combustion carbon dioxide capture. These processes are typically carried out in absorption columns containing trays or packing that provide interfaces for gas–liquid contacting. New devices such as membrane contactors are also emerging as alternative mechanisms for achieving separation of gases with potential cost and energy-saving benefits derived from having smaller footprints, being of lighter weight and having much larger interfacial areas. Yet in all cases, the design, cost and ability to optimize gas–liquid contactors may be limited by conventional manufacturing techniques. In this respect, 3D printing could be a mechanism by which to achieve improvements on existing technologies and more rapidly deploy novel devices. Here, the authors describe their efforts to date in the application of 3D printing for the fabrication of components and devices for carbon dioxide–capture applications and provide perspective on design strategies, opportunities and challenges.